Landscape Amenities Economic Assessment of Agricultural Landscapes - Vanslembrouck, Isabel; Van Huylenbroeck, Guido (Landscape Series, 2005)
Provision of landscape amenities, assured by farmers in addition to their economic function to produce food and fibre, has contributed to a reassessment of the place of agriculture in society. Farming should be regarded as 'multifunctional' whereby diverse roles fulfilled by farmers can be identified. The present book mainly tries to formulate an answer to following questions: What is the economic value for society of the farmers' role as stewards of the countryside; and under which conditions are farmers willing to provide these landscape amenities? The challenge of this research is to value the agricultural landscape, as a non-commodity output from agriculture, both from a supply and demand perspective. The main conclusions from the analysis are that: 1. Positive amenities from agricultural activities play an important role in the demand for rural tourism, and there are significant marginal benefits for the general public from the provision of landscape amenities; 2. Farmers' willingness to participate in landscape programmes depend on the trade-off with food and fibre production, on the characteristics of the proposed policies or measures, on the nature of the farm and on the profile of the farmer.